Discussão sobre a diversificação produtiva na agricultura familiar da comunidade quilombola de Jacundaí (Moju-PA) - MORAES, Richelly Valadares (2019)
The present work sought to conduct a quantitative-qualitative research in the community of Jacundaí, municipality of Moju, Northeast of the State of Pará, where it was tried to identify by which factors most of the familiar farmers of the said community can not diversify their production, investing basically in the production of cassava flour. Since agricultural production diversification presents many advantages when compared to monoculture, since it is a strategy to reduce risks and allows income throughout the year. The research was carried out through a semi-structured questionnaire and had the participation of 10 (ten) farmers, based on the Rural Participatory Diagnosis (DRP), elaborated during the researches of the Community Time Course of Rural Education, through the discipline of Pedagogical practices. The main objective of this work is to provide a discussion of other possibilities of agricultural production that involve the diversification of productive activities of cultivation and breeding in the studied community. The research developed with the use of questionnaires and interviews brought several answers to the problem raised, and it was verified that community farmers need more incentives and opportunities to achieve better results in productive activities, thus providing a sustainable development of the family and the community.